2018
DOI: 10.1186/s13071-018-3089-9
|View full text |Cite
|
Sign up to set email alerts
|

A novel candidate species of Anaplasma that infects avian erythrocytes

Abstract: BackgroundAnaplasma spp. are Gram-negative obligate intracellular bacteria transmitted by ticks. Even though numerous studies have detected DNA from Anaplasma spp. in the blood of birds, thus far mammals were the only vertebrates demonstrated to serve as competent hosts to these organisms. We report a novel candidate species of Anasplasma that was associated with cytoplasmic inclusions in the erythrocytes of an African penguin (Spheniscus demersus) in South Africa.MethodsCytoplasmic inclusions were morphologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…A recently described novel organism in erythrocytes from an African penguin ( Spheniscus demersus ) displays molecular resemblance to the Anaplasma sp. from the gopher tortoises as it is considered most closely related to the cluster comprising A. centrale , A. capra , A. marginale , and A. ovis . The intraerythrocytic organism in the tortoises was unique by molecular analysis with sequencing that indicated the organism was most closely related to but basal to a clade of the genus Anaplasma that contains A. marginale , A. ovis , and A. centrale .…”
Section: Discussionmentioning
confidence: 99%
“…A recently described novel organism in erythrocytes from an African penguin ( Spheniscus demersus ) displays molecular resemblance to the Anaplasma sp. from the gopher tortoises as it is considered most closely related to the cluster comprising A. centrale , A. capra , A. marginale , and A. ovis . The intraerythrocytic organism in the tortoises was unique by molecular analysis with sequencing that indicated the organism was most closely related to but basal to a clade of the genus Anaplasma that contains A. marginale , A. ovis , and A. centrale .…”
Section: Discussionmentioning
confidence: 99%
“…The tick O. capensis is suspected to transmit blood parasites to African penguins, such as the piroplasmid protozoan Babesia peircei (Earlé et al ., 1993), the spirochete bacterium Borrelia sp. (Yabsley et al ., 2012) and the rickettsial bacterium ‘ Candidatus Anaplasma sphenisci’ (Vanstreels et al ., 2018 a ). However, there is also speculation that the hard tick Ixodes uriae , a frequent parasite of penguins in other regions of the world, might also infect African penguins and transmit these pathogens (Earlé et al ., 1993; Peirce, 2000; Yabsley et al ., 2012; Vanstreels et al ., 2018 a ).…”
Section: Introductionmentioning
confidence: 99%
“…(Yabsley et al ., 2012) and the rickettsial bacterium ‘ Candidatus Anaplasma sphenisci’ (Vanstreels et al ., 2018 a ). However, there is also speculation that the hard tick Ixodes uriae , a frequent parasite of penguins in other regions of the world, might also infect African penguins and transmit these pathogens (Earlé et al ., 1993; Peirce, 2000; Yabsley et al ., 2012; Vanstreels et al ., 2018 a ). Other blood parasites known to infect African penguins include the haemosporidian protozoa Plasmodium spp.…”
Section: Introductionmentioning
confidence: 99%
“…nov determined in the present study are consistent with those previously reported [1], and different from the other intraerythrocytic Anaplasma spp. [20,23,[33][34][35]. These findings significantly contribute to the research on this novel zoonotic Anaplasma sp.…”
Section: Discussionmentioning
confidence: 89%